2005
DOI: 10.1057/palgrave.jors.2601923
|View full text |Cite
|
Sign up to set email alerts
|

Relevance assumed: a case study of balanced scorecard development using system dynamics

Abstract: The balanced scorecard (BSC) has become a popular concept for performance measurement. It focuses attention of management on only a few performance measures and bridges different functional areas as it includes both financial and non-financial measures. However, doubts frequently arise regarding the quality of the BSCs developed as well as the quality of the process in which this development takes place. This article describes a case study in which system dynamics (SD) modelling and simulation was used to over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(95 citation statements)
references
References 26 publications
1
82
0
4
Order By: Relevance
“…Consequently, this research suggests that, due to cognitive limitations, managers may not appreciate the significance of non-financial and leading measures, thereby defying the cause-and-effect logic built into the BSC approach and potentially reducing the benefits of using the BSC. Akkermans and van Oorschot (2005) describe a case study where a two-stage modeling process (qualitative causal loop diagramming followed by quantitative simulation) was used to overcome certain problems associated with BSC implementation. This research suggests that qualitative causal loop diagramming helps managers in identifying key variables and their causal interrelations, and the use of system dynamics simulation modeling is essential in developing a better comprehension of business dynamics, such as time delays and accumulations in the key business processes.…”
Section: Balanced Scorecard and Organizational Performancementioning
confidence: 99%
“…Consequently, this research suggests that, due to cognitive limitations, managers may not appreciate the significance of non-financial and leading measures, thereby defying the cause-and-effect logic built into the BSC approach and potentially reducing the benefits of using the BSC. Akkermans and van Oorschot (2005) describe a case study where a two-stage modeling process (qualitative causal loop diagramming followed by quantitative simulation) was used to overcome certain problems associated with BSC implementation. This research suggests that qualitative causal loop diagramming helps managers in identifying key variables and their causal interrelations, and the use of system dynamics simulation modeling is essential in developing a better comprehension of business dynamics, such as time delays and accumulations in the key business processes.…”
Section: Balanced Scorecard and Organizational Performancementioning
confidence: 99%
“…First, we would like to mention a few studies that already use system dynamics for performance management/measurement and BSC in an accounting setup. Akkermans and van Oorschot [84] show how time-lag and causal discussions from the BSC literature can be included into a system dynamics model. In close collaboration with a team from a company, Akkermans and van Oorschot [84] built a comprehensive BSC dynamic system model.…”
Section: Building the System Dynamic Balanced Scorecard: The Study Dementioning
confidence: 99%
“…Complex systems are 'complex' because of the multiple feedback or interactions among the various components. It was suggested that the issues in identifying the right measures to be selected, should there enough or more and the impact of delays could be resolved by adopting simulation using SD methodology into BSC framework [21]. Principally, SD is defines as method of studying a complex problem by explaining the structure of interactions among all the compositions as well as the behavior.…”
Section: System Dynamics Modellingmentioning
confidence: 99%